Abscisic Acid Regulates Auxin Distribution to Mediate Maize Lateral Root Development Under Salt Stress - Lu, Chongchong; Chen, Mo-Xian; Liu, Rui; Zhang, Lin; Hou, Xuanxuan; Liu, Shouxu; Ding, Xinhua; Jiang, Yong; Xu, Jiandi; Zhang, Jianhua; Zhao, Xiangyu; Liu, Ying-Gao (Frontiers in Plant Science, 2019)
The root is an important organ for plants. Lateral root (LR) initiation and development play a central role in environmental adaptation. The mechanism of LR development has been well investigated in Arabidopsis. When we recorded the distribution of auxin and ABA in maize, we found that the mechanism differed from that of Arabidopsis. The distribution of ABA and auxin were independent of each other at the primary root (PR) and LRs. Auxin localization was observed below the quiescent centre of the root tip, while ABA localized at the top of the quiescent centre. Furthermore, NaCl inhibits LR initiation by enhancing ABA accumulation, which mainly regulates the distribution of auxin, while the biosynthesis of auxin is inhibited by ABA in Arabidopsis. The polar localization of ZmPIN1 in maize was disturbed by NaCl or exogenous ABA. The inhibitor of ABA biosynthesis, fluridone, or the ABA biosynthesis mutant vp14 relieved the phenotype of NaCl treatment. All evidence suggested that NaCl promoted ABA accumulation in LRs, and ABA changed the polar location of ZmPIN1 and then disturbed the distribution of auxin and inhibited LR initiation and development.